La corrupción de la beneficencia en los debates parlamentarios del Trienio Liberal en España (1820-1823). - FERIA LORENZO, DIEGO JOSÉ; RAMOS COBANO, CRISTINA (Cultura de los Cuidados, 2024)
One of the main novelties in the parliamentary debate of the Charities Act during the Liberal Triennium consisted in denouncing the irregularities committed in such establishments. The main goal of this work is to analyse those denounces according to a triple differentiation: those regarding an irregular management of the economic resources; those concerning the council management; and those relating to ill-treatment in the charity houses. The parliamentary debates of the Liberal Triennium in the Charity Law constitute the main source of the study. Methodologically, the analysis of the interventions of the deputies who participated in the elaboration of said regulations is addressed. Being assumed as natural, such irregularities had never been denounced before by the Members of Parliament, which evidences a substantial change in the will of controlling the economic management of such establishments, as well as the caretakers' behaviour.